The Courage to Preach in the Digital Age - Sigmon, Casey T. (Religions, 2023)
This article is an invitation to truly postmodern conversational approaches to preaching beyond a monological modern mass media sermon dressed up in conversational style. This involves proposing a new who and how for preaching in the digital age, resulting in a New (Media) homiletic. Engaging with Parker J. Palmer’s The Courage to Teach, this article first explores issues with the traditional top-down model for preaching solidified during the age of mass media technoculture. Next this article names some stumbling blocks to dialogical preaching in a mainline Protestant US context. Then this article explores what difference the implementation of Palmer’s Community of Truth model could make for preaching in this digital age. The technoculture of social media allows for and expects preachers to be more conversational in the who and how of sermon delivery, preparation, and feedback.